THE FATE NOTION ON DERZIZÂDE ULVÎ’S DIVÂN - Vildan ÖZMEN (Fırat University, 2020)
At classical Turkish poem cosmic universe and revelant factors, were taken in hand generally beloved and love based cases. Fate which is one of these factors, is mentioned frequently at classical Turkish poem and is a notion involving broad meaning. This word in the meaning of skype was entreated with its aspects of colour, brightness, shape, movement, hightness and various similarities. Sometimes destiny, fortune, luck, World were used consisting similar meanings by divan poets; human became complain reason because of the believe of being effect to his destiny. In this study the notion fate: couplets had been correlated with various plans like “dome, roof, bottle, housetop, mirror, ball, headsman, vessel, tent, dining table, throne, castle, cevşen, shield, palace, pouch, pigeon, horse, elephant, peacock, and old woman, crown.” In the first episode an information had been given about Ulvî’s life: subsequently the Notion of fate with which smilitude, figüre of speech and metaphor had been handled was evaluated under various titles. The target of this study is having information both point of view of the poet and dream world and also giving an idea about how the Notion of fate was comprehended in divan poem.